LEGAL REGULATIONS FOR THE GENERAL ELECTION SYSTEM IN INDONESIA FROM THE 1955 ELECTION TO THE CONCURRENT ELECTION OF 2019 - Rannie, Mahesa (Nurani: jurnal kajian syari’ah dan masyarakat, 2020)
Throughout its history, Indonesia has held general elections many times from 1955 to 2019. During that long period of time, Indonesia implemented a different electoral system at each election. The arrangement of the electoral system in Indonesia always changes from time to time in each election administration. In the process of changing the laws and the regulations for every election, there has always been legal political dynamics. After the 2014 elections, there have been changes regarding the conduct of elections in Indonesia. The Constitutional Court (MK) granted the petition for a judicial review of Law Number 42 of 2008 concerning the Election of President and Vice President in 2014, so that the implementation of elections in Indonesia entered a new phase in 2019 and beyond. In 2019, for the first time Indonesia held simultaneous elections. The methodology used in this study is normative. The approaches used in this study are the historical approach, the statute approach, the legal analysis approach, and the conceptual approach. Legal arrangements regarding the conduct of elections always change, starting from the highest level of legislative regulations to the lowest (from the laws to the General Election Commission regulations, presidential decrees, ministerial regulations, or other regulations). The changes in the regulations regarding the implementation of elections in Indonesia have been present since the time of the 1955 elections until the 2019 elections. Since the implementation of the 1955 elections, Indonesia has always practiced a proportional electoral system, the electoral system that is considered suitable to be applied in Indonesia. This proportional electoral system is practiced with various modifications (both the open proportional electoral system and the closed proportional system). There are even district elements in the proportional electoral system in Indonesia, for example there are electoral districts that can be equated with districts in the district electoral system. The practice of the electoral system to be used in the elections in Indonesia is almost always subject to debate, both among constitutional law intellectuals and politics.